Policy and perspective on outpatient programs for autologous hematopoietic cell transplantation and immune-effector cell therapy administration - Goldsmith, Scott R.; San-Rozano, May; Katindoy, Justine; Rattanapichetkul, Janet; Rosenzweig, Michael (Frontiers in Immunology, 2024)
High-dose chemotherapy with autologous hematopoietic cell transplantation (AutoHCT) has long been an integral treatment modality for multiple myeloma and non-Hodgkin lymphoma. Over the past 25 years, numerous institutions have shifted this practice from requiring hospitalization to one that can be performed in an ambulatory setting, resulting in cost savings and improved quality of life for patients. The recent advent immune-effector cell (IEC) therapies and expansion of their indications is changing the treatment landscape for hematologic and non-hematologic malignancies. However, current financial models and reimbursement structures threaten the viability and sustainability of this treatment modality should it continue to require inpatient administration and management. This threat is leading institutions to develop outpatient IEC programs based off the outpatient AutoHCT templates. Integral to the success of both is a cohesive program with outpatient-specific standard operating protocols, highly-trained providers and staff with expertise specific in these treatment modalities, evidenced-based supportive care and prophylaxis plans, extensive caregiver vetting and education, and the infrastructure to support all individuals involved. In this policy and practice review we provide an overview of the guidelines and published academic experiences, give a perspective-based description of the roles and responsibilities of the individuals involved in this process at our institution, and highlight actionable recommendations that could allow for the dissemination and implementation of outpatient AutoHCT and IEC programs more broadly.